PRIORITIZATION OF BALANCED SCORECARD MEASUREMENT INDICATORS AS A PROCESS MANAGEMENT APPROACH VIA FUZZY AHP: CASE STUDY IN AUTOMOTIVE INDUSTRY - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2014)
This article seeks to evaluate organization's performance and minimize uncertainties and variations by presenting a methodology using fuzzy AHP in four dimensions of balanced scorecard. The purpose of this study is to prioritize the performance measurement indicators in organization that is producing automobiles for domestic and foreign market of Turkey. The case study along with the methodology used in this research can be a guideline for professionals and researchers for evaluating the processes and performance measurement indicators both in manufacturing and service organizations. The methodology of this study provides flexibility, agility, efficiency and effectiveness for preferences of the decision makers.
Keywords: balanced scorecard; fuzzy; automotive; ANALYTIC HIERARCHY PROCESS; PERFORMANCE-MEASUREMENT; MANUFACTURING-INDUSTRY; SELECTION